The Retrosynthesis Mindset: A Problem-Solving Tool - Choo, Yvonne S. L.; Kolanowski, Jacek L.; Milić, Jovana V.; Fung, Fun Man (Synlett, 2024)
Retrosynthesis refers to the process of deconstructing a target molecule step by step until simpler and commercially available synthetic precursors are identified to develop a valid synthetic pathway. As a powerful problem-solving tool, it has gradually been expanded to other fields of chemistry. The application of a ‘retrosynthesis mindset’ can be relevant beyond chemistry, such as in education, research management, and science advice. In this Letter, we discuss the concept of the retrosynthesis mindset and its implications within and beyond chemistry in the hope of highlighting a broader potential and encouraging the adoption of such a mindset to enhance problem solving and strategic planning across disciplines.1 Introduction2 Retrosynthesis Education3 Retrosynthesis Within and Beyond the Lab4 Conclusion
Keywords: retrosynthesis mindset; problem-solving tool; retrosynthesis; education; research management; science advice